A high performance DTC strategy for torque ripple minimization using duty ratio control for SRM drive - P., Veena; Jeyabharath, R.; M., Rajaram; Sivanandam, S.N. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.